Positive Tuberculin and Primary Tuberculosis Frequency among Non-BCG Children of 0-4 years (Preliminary Report) - Jati Soenarto; Achmad Surjono; Djauhari Ismail; Sunartini Sunartini; Soekardi Dirdjohusodo (Indonesian Pediatric Society, 1976)
The tuberculin test, rontgen photos, and nutritional condition of babies and pre-school children admitted to the Department of Child Health, University of Gadjah Mada Hospital, revealed: - A very high tuberculin index among the children examined, especially those under one year of age, much higher than the figures ever to be reported in Indonesia. - A direct correlation between the size of induration and the likelihood of finding pulmonary abnormalities. - A close relationship between deficient nutritional status and rontgenologic abnormalities of the lungs. We think that deficient nutritional status develops due to the presence of tuberculosis infection. Based on the factors mentioned above, in the national campaign against tuberculosis the following should be considered : - BCG at the earliest possible moment (neonatal period/life). - INH chemoprophylactic to all positive contact children will effectively prevent clinical manifestation as well as improve nutritional status.